UBUNGAN KEAHLIAN USE DENGAN PARTISIPASI USER DAN H BUNGAN PARTISIPASI USER DE GAN VARIABEL LAIN - Indriasari Kusumadewi (Media Riset Akuntansi, Auditing & Informasi, 2003)
User participation in information system considered as an essential key to system success. This research suggested that user expertise will effect user participa-tion in information system development and user participation is pot having direct rule to system success but it will be mediated by variables, such as ta uncertainty, system acceptance and user satisfaction.The result supports the similar research conducted by p vious researchers. Data analysis of 184 respondents from various characteristics concludes that user expertise correlates positively in stimulating user particcipation in Oformation system. In addition, user participation in information system have positive correlation with task certainty, system acceptance and user satisfaction.Keywords: user expertise, user participation, task uncertainty, user satisfaction, information system development.